APPLICATION OF INNOVATION MANAGEMENT STRATEGIES FOR THE COMPETITIVENESS OF ONLINE PRODUCT COMPANIES - Bondan Subagyo; Nur Hidayati; Triyani Capeg Hadmandho (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
In the modern industrial world, there is intense competition among all businesses as they strive to become more competitive in order to survive and compete on the worldwide market. Information technology is a vital component of the corporate world, particularly in light of the fiercely competitive commercial environment. Business strategy matters become more crucial to firm management because of this competitiveness. Innovation management strategy is an important step for online product companies to increase their competitiveness in the market. By implementing the right innovation strategy, companies can create unique products or services, meet customer needs, and face competition with competitors. By implementing the right innovation management strategy, online product companies can increase their competitiveness in the market. Implementing market orientation and innovation, adopting advanced technology, developing new business models, tailored marketing approaches, and product and service innovation are some of the steps that can help companies achieve these goals.